Boron-Oxygen Defect Formation Rates and Activity at Elevated Temperatures. (August 2016) - Hamer, Phillip; Nampalli, Nitin; Hameiri, Ziv; Kim, Moonyong; Chen, Daniel; Gorman, Nicholas; Hallam, Brett; Abbott, Malcolm; Wenham, Stuart
Abstract: In this work the dependence of the slow boron-oxygen defect formation rate on excess carrier density is examined in p-type Cz silicon. In order to examine behavior at elevated temperatures simple models are developed to simulate the injection-level dependent lifetime of samples at a range of temperatures and active defect concentrations. These models are then verified against experimental data. Based on these models it is possible to clearly observe a quadratic dependence of defect formation rate upon total hole concentration over a range of temperatures. The implications of a hole (and hence excess carrier (Δ n )) dependent defect formation rate, combined with the temperature dependence of defect activity are then discussed. It is demonstrated how a dependence of formation rate upon hole concentration increases the rate of defect formation and mitigation of carrier-induced degradation in samples with reduced saturation current density during anneals at elevated temperatures and illumination intensities.